2019
DOI: 10.1590/1678-4685-gmb-2018-0212
|View full text |Cite
|
Sign up to set email alerts
|

The perturbed expression of m6A in parthenogenetic mouse embryos

Abstract: Parthenogenetically activated oocytes cannot develop to term in mammals owing to abnormal epigenetic modifications. Methylation of the N6 position of adenosine (m6A) is a post-transcriptional epigenetic modification of RNA. To investigate the role of m6A methylation in parthenogenetic (PA) embryonic development, we analyzed METTL3, METTL14, FTO, ALKBH5, YTHDF2, IGF2BP1, and IGF2BP2 expression by quantitative real-time PCR. These genes were found dynamically expressed during the 2-cell, 4-cell, 8-cell, and blas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Increasing data have demonstrated that RNA modification is a dynamic process involved in the regulation of a variety of physiological processes (Motorin and Helm, 2011;Chan et al, 2012;Meyer and Jaffrey, 2014;Kirchner and Ignatova, 2015). Our previous data confirmed that m6A modification is a dynamic process that occurs during mouse embryonic development (Hao et al, 2019). This finding indicated that the methylation status of m6A was dynamically regulated by m6A-related genes during embryonic development (Faulds et al, 2018).…”
Section: Expression Pattern Of the Genes Responsible For Regulating The M6a Modificationsupporting
confidence: 80%
“…Increasing data have demonstrated that RNA modification is a dynamic process involved in the regulation of a variety of physiological processes (Motorin and Helm, 2011;Chan et al, 2012;Meyer and Jaffrey, 2014;Kirchner and Ignatova, 2015). Our previous data confirmed that m6A modification is a dynamic process that occurs during mouse embryonic development (Hao et al, 2019). This finding indicated that the methylation status of m6A was dynamically regulated by m6A-related genes during embryonic development (Faulds et al, 2018).…”
Section: Expression Pattern Of the Genes Responsible For Regulating The M6a Modificationsupporting
confidence: 80%
“…The function of m6A modification is determined by writers, erasers and readers, and the abnormality of its regulation mechanism is related to cancer [ 23 , 26 , 27 ]. In order to reveal the role of m6A modification in CRC, the gene expressions of m6A binding proteins were compared by RNA-seq in TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…“Eraser” demethylases (e.g., FTO, ALKBH5, and ALKBH3) can remove the m6A modification, and the m6A residue can be recognized by “readers” (e.g., YTHDC1/2, YTHDF1/2/3, IGF2BP1/2/3, HNRNP, and eIF3) [ 23 ]. m6A plays important roles in mRNA stabilization, splicing, degradation, and translation efficiency via altering target gene expression [ 24 , 25 ], and its function has been explored in various biological processes, including stem cell differentiation [ 26 ], embryonic development [ 27 ], DNA damage [ 28 ], and tumor progression [ 23 ], among others. As an important m6A regulator enzyme, the methyltransferase, METTL3, can promote tumor progression by regulating downstream target genes in leukemia [ 29 ], colorectal cancer [ 30 , 31 ], bladder cancer [ 32 ], and gastric cancer [ 33 ]; however, the relationship between the m6A writer, METTL3, and VM formation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence (IF) staining is an important method for measuring protein expression in embryos, and has been used in our previous studies (Gao et al, 2019; Hao et al, 2019; Liang et al, 2017; Yuan et al, 2017) and other related studies (Amouroux et al, 2016; Inoue & Zhang, 2011; Sakashita et al, 2014). To detect expression of apoptotic proteins in MII oocytes by IF staining in this study, we analyzed the P53 level of 21 MII oocytes of 100 μM PB1 group and 21 MII oocytes of control group, the caspase‐3 level of 24 MII oocytes of 100 μM PB1 group and 23 MII oocytes of control group.…”
Section: Methodsmentioning
confidence: 99%